The Effect of Digital Campaign on Purchase Decisions through Consumer Purchase Intention for GrabFood Application - Aulia Marhamah; Btari Mariska Purwaamijaya; Rusani Jaelani (Indonesian Journal of Digital Business, 2024)
The post-pandemic economic recovery is inseparable from the influence of digitalization, the phenomenon of digitalization has an impact on the behavior of consumers who want something quickly, efficiently and flexibly. This also has an impact on consumer behavior patterns in consuming food where people use food delivery services through applications. The fact is that Indonesian people use the delivery service at least once a week. Indonesia is also the largest market share for food delivery services in Southeast Asia. Food delivery service providers in Indonesia are GoFood, GrabFood and ShopeeFood. GrabFood dominates the competition for food delivery services in Southeast Asia but not in Indonesia. This can be a threat to GrabFood because it cannot control the highest market share in Southeast Asia. consumer buying interest. This study used a quantitative method with nonprobability sampling and sample selection was taken with special criteria as many as 90 respondents who were users of the GrabFood application. Data collection used an online questionnaire which was distributed via the Google form link to the respondents. The analytical method used is path analysis to see the mediating effect of buying interest variables with the help of the IBM SPSS 25 program. positive effect on purchasing decisions. Then buying interest is proven to be able to mediate the influence of digital campaigns on purchasing decisions.